Comparing Ultra-hypofractionated Proton versus Photon Therapy in Extremity Soft Tissue Sarcoma - Rehema Thomas, MD; Hao Chen, PhD; Emile Gogineni, DO; Aditya Halthore, MD; Bethlehem Floreza, BS, RT(T), CMD; Temiloluwa Esho-Voltaire, BS, CMD; Arcelia Weaver, RT(T), CMD; Sara Alcorn, MD, PhD, MPH; Matthew Ladra, MD, MPH; Heng Li, PhD; Curtiland Deville Jr, MD (International Journal of Particle Therapy, 2023)
Purpose: Recent single institution, phase II evidence has demonstrated the feasibility and efficacy of ultra-hypofractionated, preoperative photon therapy in 5 fractions for the treatment of soft tissue sarcoma (STS). Our purpose was to evaluate the dosimetric benefits of modern scanning beam proton therapy compared with conventional photon radiation therapy (RT) for the neoadjuvant treatment of adult extremity STS. Materials and Methods: Existing proton and photon plans for 11 adult patients with STS of the lower extremities previously treated preoperatively with neoadjuvant RT at our center were used to create proton therapy plans using Raystation Treatment Planning System v10.A. Volumes were delineated, and doses reported consistent with International Commission on Radiation Units and Measurements reports 50, 62, and 78. Target volumes were optimized such that 100% clinical target volume (CTV) was covered by 99% of the prescription dose. The prescribed dose was 30 Gy for PT and RT delivered in 5 fractions. For proton therapy, doses are reported in GyRBE = 1.1 Gy. The constraints for adjacent organs at risk (OARs) within 1 cm of the CTV were the following: femur V30Gy ≤ 50%, joint V30Gy < 50%, femoral head V30Gy ≤ 5cm3,stripV12 ≤ 10%, and skin V12 < 50%. Target coverage goals, OAR constraints, and integral dose were compared by Student t test with P < .05 significance. Results: A minimum 99% CTV coverage was achieved for all plans. OAR dose constraints were achieved for all proton and photon plans; however, mean doses to the femur (10.7 ± 8.5 vs 16.1 ± 7.7 GyRBE), femoral head (2.0 ± 4.4 vs 3.6 ± 6.4 GyRBE), and proximal joint (1.8 ± 2.4 vs 3.5 ± 4.4 GyRBE) were all significantly lower with PT vs intensity-modulated radiation therapy (IMRT) (all P < .05). Integral dose was significantly reduced for proton vs photon plans. Conformity and heterogeneity indices were significantly better for proton therapy. Conclusion: Proton therapy maintained target coverage while significantly reducing integral and mean doses to the proximal organs at risk compared with RT. Further prospective investigation is warranted to validate these findings and potential benefit in the management of adult STS.